GENETIC VARIATION WITHIN THE AQUATIC PLANT SPECIES CRYPTOCORYNE ×PURPUREA IN TASIK BERA, MALAYSIA AS REVEALED BY RAPD ANALYSIS - Ahmad Sofiman Othman; Yu Choo How; Chin Choke Lin; Mashhor Mansor (Tropical Life Sciences Research, 2007)
Genetic variation of two natural populations of the rare aquatic plant species Cryptocoryne ×purpurea were investigated using random amplified polymorphic DNA (RAPD) markers. Four random primers generated a total of 57 bands and 49 (86%) of them were polymorphic indicating considerable genetic variation at the species level. A Neighbor-Joining (NJ) tree constructed using genetic similarities data separated the samples into two distinct groups each representing a single population. Two-dimensional PCO graph generated from genetic similarity data was also in agreement with the NJ tree topology. Analysis of molecular variance (AMOVA) showed that a large proportion of the genetic variation (67%) resided between populations while only 33% of the genetic variation resided within population. The low level of genetic diversity among individuals was likely generated from somatic mutation since this hybrid species exhibited high pollen sterility. However, separate hybridization events followed by population isolation and subsequent independent accumulation of somatic mutations could have resulted in the high genetic variation between populations. Variasi genetik dua populasi semulajadi tumbuhan akuatik yang jarang ditemui Cryptocoryne ×purpurea telah dikaji dengan menggunakan penanda DNA polimorfik amplikasi rawak (RAPD). Empat pencentus rawak menjana sejumlah 57 jalur dan 49 (86%) daripadanya adalah polimorfik menggambarkan variasi genetik yang tinggi untuk spesies ini. Rajah pohon berdasarkan kaedah Neighbor-Joining (NJ) dijana menggunakan data kesamaan genetik membezakan sampel-sampel ke dalam dua kelompok berbeza setiap satunya untuk populasi tunggal. Graf PCO dua-dimensi yang dijana menggunakan data kesamaan genetik juga serasi dengan topologi rajah pohon NJ. Analisis varians molekul (AMOVA) menunjukkan bahawa sebahagian besar variasi genetik (67%) berada antara populasi sementara hanya 33% daripada variasi genetik berada di dalam populasi. Aras genetik antara individu yang rendah terhasil daripada mutasi somatik memandangkan spesies hybrid ini menunjukkan kesterilan debunga yang tinggi. Namun, peristiwa hibridisasi yang berbeza diikuti pemencilan populasi dan pengumpulan mutasi somatik yang tak bersandaran mungkin telah menyebabkan variasi genetik antara populasi yang tinggi.